Review of Livestock Semen Extension and Cryopreservation of Spermatozoa - S. O. Oyewumi,; A. O. Akintunde,; G. O. Tayo,; L. C. Ndubuisi-Ogbonna,; A-R. Abdullah, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The need for livestock sustainability and conservation of genetic resources, artificial dissemination seeing to be a viable tool/means in achieving this whole paying much attention to effective semen extension and cryopreservation techniques. The study reviewed the challenges associated with semen extension and cryopreservation and solutions were proffered to the identified challenges. The research community have observed that in the process of extension and cryopreservation of semen, the specimen is predisposed to detrimental effects of ice crystal formation, hyper-osmosis, alterations in the integrity of sperm cells and denaturation, important to the problem associated with cold stock during cooling, and relative in the availability of commercial extenders and powered especially in the developing countries. The solutions proffered include the embrace of using phytogenic and natural products in semen extension and research stations where alternative power sources could be implored. It is concluded that for effective conservation of genetic resources and breeding, assisted reproductive technologies with vital emphasis on quality semen extension and cryopreservation in livestock should be embraced.